Erylosides F8, V1–V3, and W–W2 – New triterpene oligoglycosides from the Carribean sponge Erylus goffrilleri. (8th September 2017) - Antonov, Alexandr S.; Kalinovsky, Anatoly I.; Afiyatullov, Shamil S.; Leshchenko, Elena V.; Dmitrenok, Pavel S.; Yurchenko, Ekaterina A.; Kalinin, Vladimir I.; Stonik, Valentin A.
Abstract: Seven new triterpene glycosides, erylosides F8 (1 ), V1 (2 ), V2 (3 ), V3 (4 ), W (5 ), W1 (6 ) and W2 (7 ), were isolated from a Carribean sponge Erylus goffrilleri collected from the Carribean Sea near the Arrecife-Seco reef (Cuba). Structures of the glycosides were determined using 1 H and 13 C NMR spectroscopy, including 2D NMR procedures ( 1 H– 1 H COSY, 1 H– 13 С HMBC, 1 H– 13 С HSQC and NOESY) and HR ESI mass spectrometry. Erylosides1 and4 have 14-carboxy-24, 25-dimethyllanost-8(9)-en-3β, 25-diol as aglycone whereas glycosides2, 3, 5, 6 and7 are 14-carboxy-24-acetoxy-24-methyllanost-8(9)-en-3β-ol glycoconjugates. Cytotoxic activities of the isolated compounds against Ehrlich carcinoma cells and hemolysis were examined and their dependence on eryloside structure was evaluated. Graphical abstract: Highlights: Seven new triterpene glycosides were isolated from Erylus goffrilleri. Three of them are tetraosides, another three ones are triosides and one is a bioside. The presence of an O-acetic group at C-6 of first monosaccharide is unique for sponge triterpene glycosides.